Inverse correlation between the extent of N-glycan branching and intercellular adhesion in epithelia: contribution of the Na,K-ATPase β(1) subunit - Vagin, Olga (2007)
The majority of cell adhesion molecules are N-glycosylated but the role of N-glycans in intercellular adhesion in epithelia remains ill-defined. Reducing N-glycan branching of cellular glycoproteins by swainsonine, the inhibitor of N-glycan processing, tightens and stabilizes cell-cell junctions as detected by a 3-fold decrease in the paracellular permeability and a 2- to 3-fold increase in the resistance of the adherens junction proteins to extraction by non-ionic detergent. In addition, exposure of cells to swainsonine inhibits motility of MDCK cells. Mutagenic removal of N-glycosylation sites from the Na,K-ATPase β(1) subunit impairs cell-cell adhesion and decreases the effect of swainsonine on the paracellular permeability of the cell monolayer and also on detergent resistance of adherens junction proteins, indicating that the extent of N-glycan branching of this subunit is important for intercellular adhesion. The N-glycans of the Na,K-ATPase β(1) subunit and E-cadherin are less complex in tight renal epithelia than in the leakier intestinal epithelium. The complexity of the N-glycans linked to these proteins gradually decreases upon the formation of a tight monolayer from dispersed MDCK cells. This correlates with a cell-cell adhesion-induced increase in expression of GnT-III (stops N-glycan branching) and a decrease in expression of GnTs IVC and V (promote N-glycan branching) as detected by real-time quantitative PCR. Consistent with these results, partial silencing of the gene encoding GnT-III increases branching of N-glycans linked to the Na,K-ATPase β(1) subunit and other glycoproteins and results in a 2-fold increase in the paracellular permeability of MDCK cell monolayers. These results suggest epithelial cells can regulate tightness of cell junctions via remodeling of N-glycans, including those linked to the Na,K-ATPase β(1)-subunit.